2005
DOI: 10.1111/j.1470-6431.2005.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of an emotion model based on colour combinations

Abstract: The purpose of this study was to develop an emotion model based on the colour combinations popularly used for interior coordination in Korea. To summarize, the emotion model had the following features: (1) It consisted of three axes named as ‘soft–hard’ (first dimension), ‘light–heavy’ (second dimension) and ‘splendid–sober’ (third dimension). (2) The emotion descriptors were categorized into nine emotion groups and matched with the representing colour combinations. (3) This emotion model had a one‐to‐multipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…This was also the case for pink where its lightness was said to ''tone down'' the aggressive and active feelings associated with red and make it more feminine (see also Lee and Lee, 12 Garret and Brooks, 13 Weller and Livingston. 14 ''If it's a light red it's softer, not as strong emotions, although once it becomes pink it's more feminine''-Natalie…”
Section: Pinkmentioning
confidence: 94%
“…This was also the case for pink where its lightness was said to ''tone down'' the aggressive and active feelings associated with red and make it more feminine (see also Lee and Lee, 12 Garret and Brooks, 13 Weller and Livingston. 14 ''If it's a light red it's softer, not as strong emotions, although once it becomes pink it's more feminine''-Natalie…”
Section: Pinkmentioning
confidence: 94%
“…Another finding is the existence of universal colour preferences, although national variations in consumer preferences are detected as well. The first findings could be explained by unconscious or conscious colour effects, while the latter preferences could be the result of semiconscious colour learning . Innate colour effects could also explain why the cold and short‐wavelength colours like blue and green are generally preferred to the warm and long‐wavelength colours red and yellow .…”
Section: Three Means Of Packaging Coloursmentioning
confidence: 99%
“…Figure stresses that packaging colours influence emotions at least at some level, the responses being unconscious (innate), semiconscious (culturally learned) or conscious (personal colour preferences based on personal experiences, for example) …”
Section: Three Means Of Packaging Coloursmentioning
confidence: 99%
“…Therefore, they extended their studies looking into the differences in lightness and chroma at 0 hue angle describing the differences between the three regions (Xin et al, 2004a;Xin, Cheng, Taylor, Sato & Hansuebsai, 2004b). Lee and Lee (2006) found that colour emotion was highly affected by its tone. Stahre, Harleman and Billger (2004) showed that colour size is effective in terms of emotional response.…”
Section: Kaya and Eppsmentioning
confidence: 99%